Testing feedstuffs using near-infrared reflectance spectroscopy (NIRS) - Dubois, P.C.; Harbers, L.H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Over 16 years ago, an analytical instrument was developed that could rapidly determine the concentration of organic compounds from the spectra produced by the bonding between certain molecules. The instrument is based on the principle that those molecules absorb electromagnetic radiation in the infrared region. Compounds may be quantitated by using a computer to compare absorption bands in the near-infrared spectrum to those from a large calibration set of known composition. Peaks from compounds such as water, protein, fat, and carbohydrate may be translated into nutrient components such as moisture, crude protein, crude fat, acid detergent fiber, etc. all this can be accomplished in minutes rather than the hours or days required for the routine chemical analyses presently available.
Keywords: Beef; near-infrared reflectance spectroscopy (NIRS); Feedstuffs